Preparation and Properties of NH2-SBA-16@IAA@CS Coating - Yang, Yidan; Luo, Lingyun; Zhou, Qiang; Deng, Huiyaun; Liu, Xiaonan (International Journal of Materials Science and Technology Studies, 2025)
In the present study, aminoated SBA-16@indoleacetic acid-@chitosan composite (NH2-SBA-16@IAA@CS) was prepared on glass plate (supporting substrate). Indoleacetic acid (IAA) was introduced into aminoized SBA-16 (NH2-SBA-16), mixed with chitosan and coated on glass plate to form antibacterial slow-release coating. BET, XRD and FTIR results showed that IAA was successfully introduced into the aminating SBA-16 material. The antibacterial activity of the composite coating was studied using the biofilm-forming bacteria Bacillus subtilis and Escherichia coli. Under the same conditions, NH2-SBA-16@IAA@CS composite coated fiberglass board showed antibacterial activity compared with chitosan. The release time and amount of IAA in the composite material were also tested, and it was found that the release rate of IAA in the prepared composite coating was effectively reduced in the alkaline seawater. NH2-SBA-16@IAA@CS composites are promising alternatives to toxic antifouling coatings in the ocean.